(untitled) (Fiep Bulletin - online, 2011)
The benefits of the physical activity for the health and quality of life of the aged population today are had as credibilizados facts, however, the level of tack to such practical still is very low, mainly to the carriers of pain and musculoesqueléticas disfunções. Objective: to investigate the theoretical probability of that a cinesioterapeutico protocol, called Fisiomotricidade, indicated the patients with pain and functional limitation could favor autonomy functional of aged practitioners, if compared with the conventional physical activity. Methodology: One was about a transversal, comparative study and analytical, with quantitative boarding of the changeable carried through functional autonomy in the city of São Luis. The sample was constituted by 60 aged ones in the etária band of 65 the 75 years, divided in two groups: practitioners of conventional physical activity (G1), practitioners of Fisiomotricidade (G2) selected randomly, through the drawing of fiches in the places where the activities, CAISI and CIMO were carried through respectively. The instruments used for the study had been signature of the TCLE, evaluation of the Functional Autonomy for the Protocol of tests (GDLAM); For it analyzes of the data used analysis statistics in the changeable functional autonomy using descriptive and inferenciais statistical techniques, through the use of the test t-Student, thetest qui-square (for tables of contingencies 2x2), to the level of 5% of significance. Results: When analyzed the distribution of the frequency of the index of functional autonomy and age between the two groups one met p= 0,0293 for (G1) demonstrating that a relation of negative and significant dependence between age and functional autonomy in the practitioners of conventional physical activity for one exists p= 0,0188 for (G2) that it pointed with respect to a relation of positive dependence in relation the age in the practitioners of Fisiomotricidade. Conclusion: the physical activity showed to be crucial in advanced ages, exactly being this of low impact, since it in such a way keeps standards in the functional autonomy and repercussion in the improvement of the quality of life how much a conventional physical activity.